Alzheimer’s disease: relevant molecular and physiopathological events affecting amyloid-β brain balance and the putative role of PPARs - Zolezzi, Juan M.; Bastías-Candia, Sussy; Santos, Manuel J.; Inestrosa, Nibaldo C. (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s disease (AD) is the most common form of age-related dementia. With the expected aging of the human population, the estimated morbidity of AD suggests a critical upcoming health problem. Several lines of research are focused on understanding AD pathophysiology, and although the etiology of the disease remains a matter of intense debate, increased brain levels of amyloid-β (Aβ) appear to be a critical event in triggering a wide range of molecular alterations leading to AD. It has become evident in recent years that an altered balance between production and clearance is responsible for the accumulation of brain Aβ. Moreover, Aβ clearance is a complex event that involves more than neurons and microglia. The status of the blood-brain barrier (BBB) and choroid plexus, along with hepatic functionality, should be considered when Aβ balance is addressed. Furthermore, it has been proposed that exposure to sub-toxic concentrations of metals, such as copper, could both directly affect these secondary structures and act as a seeding or nucleation core that facilitates Aβ aggregation. Recently, we have addressed peroxisomal proliferator-activated receptors (PPARs)-related mechanisms, including the direct modulation of mitochondrial dynamics through the PPARγ-coactivator-1α (PGC-1α) axis and the crosstalk with critical aging- and neurodegenerative-related cellular pathways. In the present review, we revise the current knowledge regarding the molecular aspects of Aβ production and clearance and provide a physiological context that gives a more complete view of this issue. Additionally, we consider the different structures involved in AD-altered Aβ brain balance, which could be directly or indirectly affected by a nuclear receptor (NR)/PPAR-related mechanism.